Perbandingan Efektivitas Penyuluhan Demam Berdarah Dengue dengan Metode Role Play dan Metode Permainan Simulasi terhadap Perilaku Ibu tentang DBD di Kecamatan Medan Deli - Simanjuntak, Novita Hasiani (Universitas HKBP Nommensen, 2021)
Background: Dengue Hemorrhagic Fever (DHF) in Indonesia is a “re-emerging infectious disease”. DHF can be prevented by vector control. Human behavior is very influential on dengue vector control, namely the cleanliness of the house and activities. In 2017, DHF cases in Indonesia were 59,047 cases. In North Sumatra Province, there were 5,327 cases, in Medan City as many as 1216 cases, with Medan Deli District as the sub-district with the most cases, with 100 cases. Objective: This study aims to see the improvement of mother's behavior by using the roleplay method and simulation games. Methods: The research is a quasi-experimental non-equivalent group design. The target population is mothers who live in Medan Deli District. The selection of research subjects by purposive sampling, with the number of subjects in each group is 15 people. This study uses the method of role play and games as a comparison method, with a questionnaire as a measuring tool. Paired t-test to see the increase in the mean of each group, and unpaired t-test to see the difference in the mean value. Results: The results of the paired t-test data analysis found that these two methods showed significant results, with p values ​​of 0.000 and 0.001 with a mean increase in the role play method of 1.40 and the game method of 1.53. The unpaired t-test was found to have a significant difference between the average post-test scores between the role play method and the game method, the mean post-test score for the role-play method was found to be lower than the post-test score for the game method. Conclusions: Counseling using the role play method and games provides significant results in increasing maternal behavior about DHF. The game method shows a greater average increase than the role play method.